2017
DOI: 10.1186/s40851-017-0071-x
|View full text |Cite|
|
Sign up to set email alerts
|

An efficient system for homology-dependent targeted gene integration in medaka (Oryzias latipes)

Abstract: BackgroundThe CRISPR/Cas system is a powerful genome editing tool that enables targeted genome modifications in various organisms. In medaka (Oryzias latipes), targeted mutagenesis with small insertions and deletions using this system have become a robust technique and are now widely used. However, to date there have been only a small number of reports on targeted gene integration using this system. We thus sought in the present study to identify factors that enhance the efficiency of targeted gene integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 37 publications
(61 reference statements)
3
43
0
Order By: Relevance
“…The NHEJ-mediated knock-in method described here has one clear advantage over the homology-based recombination technique that was recently described by [ 5 ]. The current method does not require any DNA construction experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NHEJ-mediated knock-in method described here has one clear advantage over the homology-based recombination technique that was recently described by [ 5 ]. The current method does not require any DNA construction experiments.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Additional file 4 : Figure S2, indels were frequently introduced in the joint region, similar to the previous study [ 18 ]. For experiments in which precise knock-in is critical, methods that rely on homology-dependent repair systems (i.e., [ 5 ]) need to be employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the gene-editing tool CRISPR/Cas9 was also established in medaka and employed in multiple studies (e.g. Gutierrez-Triana et al, 2018; Letelier et al, 2018; Murakami et al, 2017; Watakabe et al, 2018). In many fields, including cancer research, medaka serves as complementary model to the well-established zebrafish (Schartl and Walter, 2016; Takeda and Shimada, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of very low efficiency KI of a gene encoding red fluorescent protein in rohu carp 34 , such advanced and fine-tuned genome editing has not been developed for farmed fish, and it may be useful to learn from protocols already established in model fish species. While only a few studies have reported HDR in medaka 35,36 , several KI-strategies have been reported in zebrafish using either donor plasmids [37][38][39] or single-stranded oligodeoxynucleotides (ssODNs) [40][41][42][43][44][45] , or both 46 . Knowledge from other fish studies are somewhat inconclusive when it comes to deciding the strategy for applying HDR in salmon, as there is a lack of consensus regarding the impact of different repair templates, homology arm length and strand complementarity in the above-mentioned studies.…”
mentioning
confidence: 99%